Processes of Lexical Archaiza-tion and Neologization in Modern Yakut Language - A. A. Skryabina (Научный диалог, 2023)
The process of redistribution between the active and passive vocabulary of modern Yakut language is being examined. The reasons for the archaization of vocabulary are identified, outdated words are classified by type and lexical-semantic groups, and a layer of lexical innovations is also identified. The material for the study consisted of lexical units from literary works, periodicals, and Yakut language dictionaries. The scientific novelty of the study lies in the comprehensive examination and classification of layers of outdated vocabulary, neologisms, and de-archaized Yakut language vocabulary. The distribution of Yakut language archaisms into 14 lexical-semantic groups has been carried out. It has been proven that neologisms arise in the Yakut language through changes in the meaning of existing words, through the infusion of other language stocks, and through the activation of derivation processes based on their own means. It has been revealed that the process of de-archaization in the Yakut language is associated with the revival of traditional foundations of material and spiritual culture of the Yakuts. The results of the study confirm the systemic nature of changes in the lexical composition of the language, as well as their interrelation between phenomena of archaization, de-archaization, and neologization.